(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The department heads and college or academic deans in most universities and colleges are the key individuals in determining the institution’s policies. Their organisational behaviour and emotional intelligence are most important in the changes that are taking place in “institutions of higher learning”. Organisations can only survive or prosper with their members behaving as good citizens by engaging in positive behaviour. Certain behaviours are expected from academic deans and faculty members alike and are abiding by the “rules and regulations of the institution”. However, employees sometimes exhibit behaviours beyond the call of duty called “Organizational Citizenship Behaviour (OCB)”. OCB is also known as extra-role behaviour. This study wants to determine the organisational relationship in SUCs among academic leaders. Do educational leaders’ “organisational citizenship behaviour and emotional intelligence” correlate? Are there significant relationships among the academic deans’ “organisational citizenship behaviour, emotional intelligence and institutional effectiveness”? The researcher uses the study’s three (3) instruments to gather data.